2005
DOI: 10.1677/joe.1.05899
|View full text |Cite
|
Sign up to set email alerts
|

Human growth hormone and insulin-like growth factor-I inhibit erythropoietin secretion from the kidneys of adult rats

Abstract: Growth hormone (GH) and insulin-like growth factor-I (IGF-I) play important roles in erythropoiesis and erythropoietin (EPO) secretion. We examined the effects of GH and IGF-I on EPO production in adult rat kidney and liver in vivo and in vitro. Male Wistar rats aged 8-10 weeks were used. Recombinant human GH (hGH) was continuously infused (20 µg/kg per h) subcutaneously for 48 h using a micro-osmotic infusion pump. Octreotide (10 µg/kg) was subcutaneously injected every 12 h beginning 12 h before the hGH trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Shamiyo et al [24] showed that administration of human growth hormone to diabetic patients with renal insufficiency and anemia led to an increase in Epo-levels. Similar results have been obtained in animal experiments of the same study group [25] . Quin et al [16] reported on an increase of EPOconcentration after treatment with IGF-1 in a patient with insulin resistance.…”
Section: Groupsupporting
confidence: 90%
“…Shamiyo et al [24] showed that administration of human growth hormone to diabetic patients with renal insufficiency and anemia led to an increase in Epo-levels. Similar results have been obtained in animal experiments of the same study group [25] . Quin et al [16] reported on an increase of EPOconcentration after treatment with IGF-1 in a patient with insulin resistance.…”
Section: Groupsupporting
confidence: 90%
“…The authors attributed the lack of haemoglobin production and haematocrit induction to the insufficient levels of circulating iron and to disturbances of the iron metabolism, a typical situation also reported during the APR (5). An induction under normoxic conditions of hepatic EPO in rats has also been described by Sohmiya and Kato (31) after injection of growth hormone. Surprisingly, the authors observed an upregulation of the EPO gene and an increase of the protein content in the livers and plasma of the treated animals with a decrease in renal production.…”
Section: Discussionsupporting
confidence: 62%
“…We demonstrated that clonogenic potential of CD34 + -expanded BFU-E was significantly higher in GHD patients treated with GH-RT for 6 months than that before therapy. It is possible that this effect might be a result of the modulatory action of GH on the production of erythropoietin (EPO), as increased concentrations of GH augment the levels of EPO in GHD patients with developed anemia [ 27 , 28 ], possibly due to increased hepatic synthesis of EPO [ 29 ]. However, in in vitro cultures containing an established amount of EPO, we observed increased growth only in the samples collected from patients treated previously with GH-RT.…”
Section: Discussionmentioning
confidence: 99%